Penerapan Cooperative Learning untuk Meningkatkan Keterampilan Berbicara Bahasa Arab: Studi Kasus di MIS Tanwirul Islam II Sampang - Hasyim Asy’ari, Moh. (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2025)
One of the skills desired by students is speaking skills in Arabic. In 2023, MIS Tanwirul Islama II Sampang students' Arabic speaking skills were quite low, because when learning Arabic, especially speaking skills, teachers did not use interesting and effective models, media, and strategies, so that students when learning Arabic were less interested in speaking Arabic. This year, MIS Tanwirul Islam II teachers tried to use an Arabic learning model that attracted students' interest in speaking Arabic by using the Cooperative Learning learning model. The type of research is a qualitative case study approach. In this study, data collection was also carried out by means of observation, interviews with the principal, teachers, and students of the madrasah, as well as conducting documentation at the MIS Tanwirul Islam II madrasah. The results of this study, with the implementation of the cooperative learning model, students learned to speak Arabic in groups so that there was an increase in speaking skills, this was proven by the enthusiasm of students when taking lessons, in addition, students' Arabic speaking skills were also getting better compared to previous years.